Digital Parenting and School Climate to Improve Discipline Character in Students - Ngulandari, Puspita Rini; Oktaviani, Maya; Elmanora, Elmanora (Journal of Family Sciences, 2024)
Family is not the only factor that can shape the character of a child's discipline. Schools where children get education and experience, can form a disciplinary character because they must comply with applicable regulations. This study aims to determine the effect of digital parenting and school climate on students' disciplinary character. The research method used an associative quantitative approach. The researcher distributed questionnaires using Google Forms. A proportionate stratified random sampling technique was used to select the sample with 251 students in seventh and eighth grades at Public Junior High School in East Jakarta. The results showed a significant simultaneous effect between digital parenting and school climate on students' disciplinary character. Digital parenting and school climate together can explain the character of discipline by 44.1 percent. So that parents need to increase assistance and control to children by implementing digital parenting. To the school it is necessary to maintain a healthy school climate to form and improve the character of discipline in students. Thus, the higher the application of digital parenting and the healthier or more open the school climate, the higher the character of discipline in students.